Legal Personality of an “Electronic Person”: Theoretical Analysis - E. S. Tiutcheva (Теоретическая и прикладная юриспруденция)
The article is devoted to the question of the possibility of using existing concepts of legal personality in the construction of the legal status of artificial intelligence (AI). The article examines the properties of AI in comparison with individuals and legal entities, and concludes that the full use of their legal personality as a legal basis for the electronic person’s legal personality is incorrect. Separately it’s considered the issue of the AI’s responsibility. The paper focuses on the prevention of mixing the concepts of the object and subject of law in relation to AI, identifies trends in the development of legal regulation of its legal personality, and concludes that in these modern conditions, the “electronic person” is closest in its content to the concept of “quasi-entity”.